Respostas
respondido por:
2
Método da adição:
x + y = 43
x - y = 7 (+)
------------------
2x = 50
x = 50/2
x = 25
x + y = 43
25 + y = 43
y = 43 - 25
y = 18
R.: x = 25 e y = 18
x + y = 43
x - y = 7 (+)
------------------
2x = 50
x = 50/2
x = 25
x + y = 43
25 + y = 43
y = 43 - 25
y = 18
R.: x = 25 e y = 18
respondido por:
3
Pelo método da substituição:
x + y = 43
x - y = 7 ------> x = 7 + y
-----------------------------------
x + y = 43
7 + y + y = 43
2y = 43 - 7
2y = 36
y = 36 / 2
y = 18
x = 7 + y
x = 7 + 18
x = 25
S = {18, 25}
x + y = 43
x - y = 7 ------> x = 7 + y
-----------------------------------
x + y = 43
7 + y + y = 43
2y = 43 - 7
2y = 36
y = 36 / 2
y = 18
x = 7 + y
x = 7 + 18
x = 25
S = {18, 25}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás